Comparative mapping of a new repetitive DNA sequence and chromosome region-specific probes unveiling rearrangements in an Amazonian frog complex - Gatto, Kaleb Pretto (2021)
The frog species Physalaemus ephippifer exists in the Amazonian region and harbors heteromorphic Z and W chromosomes. A genetic lineage closely related to this species was recognized based on its mitochondrial DNA and RADseq-style markers, but its taxonomic status is still unclear and has been referred to as Lineage 1 of “P. cuvieri”. The heteromorphic sex chromosomes found in P. ephippifer are not present in this lineage and which of its chromosome pairs is homologous to the sex chromosomes of P. ephippifer remain to be elucidated as well as the role of such a karyotypic divergence in the evolution of these frogs. Here, we described a new family of repetitive DNA and used its chromosomal sites along with the markers detected by a probe constructed from the microdissected segment of the Z chromosome of P. ephippifer to infer chromosomal homology. We also analyzed an unnamed species that is considered to be the sister group of the clade composed of Lineage 1 of “P. cuvieri” and P. ephippifer. Our results suggest that complex rearrangements involving the chromosomes that were inferred to be homeologous to the sex chromosomes of P. ephippifer have occurred during the divergence of this group of frogs.